Simalungun Batak Language Causative Construction - Immanuel Silaban; Robert Sibarani; Mulyadi; Hamzon Situmorang; Dwi Widayati (PT FORMOSA CENDEKIA GLOBAL, 2022)
The causative construction of the Simalungun language can be produced by combining clauses with cause / baen conjunctions, the use of causative analytic with permanent verbs, all; morphological causative use with (–kon) affixes; and the selection of certain lexical causative verbs that have causative meaning. The method used is the marking method applied in analyzing research data based on the problems discussed in this article. This causative construction of Simalungun Batak language can be explained through morphosyntax parameters.